Mamulengo and life stories: intercrossings that teach (Móin-Móin Magazine - Studies in the Art of Puppetry, 2020)
This article is a reflection on the fieldwork that I developed during the Masters and Performing Arts course at the University of Brasília (UnB) in the year 2017. The subject addressedin the dissertation was about the new generations of Mamulengo female giants of the city of Glória do Goitá (PE). The Mamulengo is a play of popular puppets theater of Pernambuco and as oral tradition, is permanently re-signified by its producers. Play allows participation and dialogue with the public. The relationship is dynamic, it takes place in the strengthening of the identity of a people, who through play: explicit, express and denounce values, inform their worldviews, their desires, individual and collective experiences. What we present here is an excerpt from the history of mamulengueira Cida Lopes, who through her personal narratives invites us to perceive how the relations of power and violence are perpetuated in her identity as brazilian northeastern and as black women.